Ketchikan from Ketchikan Creek, Alaska, September 19, 1908 - Cobb, John N. (John Nathan), 1868-1930 (1908)
From John Cobb field notebook: Ketchikan from the creek. Sept. 19, 1908. Ketchikan from Ketchikan Creek, 1908